Proses Disbursement dan Pencatatan Arus Kas pada Divisi Loan Processing di PT Simplefi Teknologi Indonesia - Sugiwan, As-syifa Rahma; Beny, Beny; Stella, Stella; Arilyn, Erika Jimena (Jurnal Abdimas Sosial, Ekonomi, dan Teknologi, 2023)
The end of the study period for final year-students requires them to be able to improve their abilities and knowledge to compete in the world of work. One of the facilities that provide opportunities for students to hone these skills is the MBKM program organized by the government. The purpose of this program is to provide experience and increase knowledge by being directly involved in the company's operations. This report will explain the author's experience during an internship at PT Simplefi Teknologi Indonesia as a Loan Operations Admin. The author is responsible for verifying data in the process of disbursing AwanTempo funds. In addition, the author is responsible for recording the reconciliation of the company's cash flow and cash balance every day. The non-routine work carried out by the author is documenting loan capital lender documents.